Comparison of the Effect of Hydrophilicity on Biocompatibilityand Platelet Adhesion of Two Different Kinds of Biomaterials: Effect of hydrophilicity on biocompatibility of biomaterialsRoswell - Bonakdara, Shahin; Orang, Fariba; Rafienia, Mohammad; Imani, Rana (Iranian Journal of Pharmaceutical Sciences, 2008)
Determination of blood compatibility is an important problem in blood contactingdevices. In this study, two classes of materials including polyurethane (based onpolyethylene glycol and poly tetrametylene oxide) and polyvinyl alcohol samples,with different hydrophilicity properties were synthesized and their physico-chemicalproperties were compared. Water uptake ratio, FTIR spectroscopy, and contactangle measurement were conducted. In vitrobiocompatibility experiments wereundertaken using L-929 fibroblast cell lines which demonstrated desired cellviability for all samples after 7 days. The adhesion of platelets from human plasmawas studied by optical microscopy. Blood coagulation time were also determinedwhich revealed polyurethane based poly tetramethylene oxide has better interactionby blood elements among all samples.